2019
DOI: 10.3390/microorganisms7120713
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insights into the Effects of Seasonal Temperature Variation on the Activities of Activated Sludge

Abstract: It is well acknowledged that the activities of activated sludge (AS) are influenced by seasonal temperature variation. However, the underlying mechanisms remain largely unknown. Here, the activities of activated sludge under three simulated temperature variation trends were compared in lab-scale. The TN, HN3-H, and COD removal activities of activated sludge were improved as temperature elevated from 20 °C to 35 °C. While, the TN, HN3-H, COD and total phosphorus removal activities of activated sludge were inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…However, under BPA stress, the abundances of these dominant genera decreased significantly, while different concentrations of BPA showed different population niches. Consistent with the research results of Ai et al, the dominant bacterial genera in artificial sewage domesticated sludge were Labilithrix and Ferribacterium [54].…”
Section: Survival Of Rhodococcussupporting
confidence: 90%
See 1 more Smart Citation
“…However, under BPA stress, the abundances of these dominant genera decreased significantly, while different concentrations of BPA showed different population niches. Consistent with the research results of Ai et al, the dominant bacterial genera in artificial sewage domesticated sludge were Labilithrix and Ferribacterium [54].…”
Section: Survival Of Rhodococcussupporting
confidence: 90%
“…In a study on autotrophic denitrification sludge, Curvibacter was found to be beneficial to improving the nitrate removal rate of sludge [63]. Acinetobacter and Comamonas play key roles in the removal of ammonia nitrogen and phosphorus under aniline stress [54]. Sphingobium is the dominant bacterial genus for the treatment of pharmaceutical wastewater in membrane bioreactors [64].…”
Section: Survival Of Rhodococcusmentioning
confidence: 99%
“…In these experiments, the amount of each bottle of culture solution was 150 mL and the tests were done in triplicate. The method of optimization was referring to previous reports [26,27], and the concentrations of COD were measured by using potassium dichromate method [28]. LZH-9 culture solution was inoculated to LB medium.…”
Section: Cod Removal Efficiency Experimentsmentioning
confidence: 99%
“…Gene abundance evaluation and species annotation were eventually performed. The method details were described in the previous studies (Ai et al 2019…”
Section: Metagenomic Sequencingmentioning
confidence: 99%